A tandem dye-sensitized photoelectrochemical cell for light driven hydrogen production. Issue 5 (5th April 2016) - Sherman, Benjamin D.; Bergkamp, Jesse J.; Brown, Chelsea L.; Moore, Ana L.; Gust, Devens; Moore, Thomas A.
Abstract : A tandem cell incorporating two dye-sensitized photoanodes produces H2 from hydroquinone using only light energy and no applied electrical bias. Abstract : Combining a dye-sensitized photoelectrochemical cell for hydrogen production based on a SnO2 photoanode in series with a dye-sensitized photovoltaic solar cell using a TiO2 photoanode yields a tandem system for the generation of H2 from hydroquinone using only light energy and no applied electrical bias. To target distinct portions of the solar spectrum, a more blue-absorbing free base porphyrin and a more red-absorbing Si phthalocyanine chromophore are used at the two photoelectrodes. With incorporation of a suitable water oxidation catalyst, a similar approach could enable tandem photochemical water splitting without the need for p-type semiconductors.